Sleep Deprivation and Time-Based Prospective Memory - Esposito, Maria José; Occhionero, Miranda; Cicogna, PierCarla (Sleep (New York, N.Y.), 2015)
To evaluate the effect of sleep deprivation on time-based prospective memory performance, that is, realizing delayed intentions at an appropriate time in the future (e.g., to take a medicine in 30 minutes). Between-subjects experimental design. The experimental group underwent 24 h of total sleep deprivation, and the control group had a regular sleep-wake cycle. Participants were tested at 08:00. Laboratory. Fifty healthy young adults (mean age 22 ± 2.1, 31 female). 24 h of total sleep deprivation. Participants were monitored by wrist actigraphy for 3 days before the experimental session. The following cognitive tasks were administered: one time-based prospective memory task and 3 reasoning tasks as ongoing activity. Objective and subjective vigilance was assessed by the psychomotor vigilance task and a visual analog scale, respectively. To measure the time-based prospective memory task we assessed compliance and clock checking behavior (time monitoring). Sleep deprivation negatively affected time-based prospective memory compliance (P < 0.001), objective vigilance (mean RT: P < 0.001; slowest 10% RT: P < 0.001; lapses: P < 0.005), and subjective vigilance (P < 0.0001). Performance on reasoning tasks and time monitoring behavior did not differ between groups. The results highlight the potential dangerous effects of total sleep deprivation on human behavior, particularly the ability to perform an intended action after a few minutes. Sleep deprivation strongly compromises time-based prospective memory compliance but does not affect time check frequency. Sleep deprivation may impair the mechanism that allows the integration of information related to time monitoring with the prospective intention.